Entrepreneurial Intentions of Japanese University Students: Entrepreneurial Self-Perception and the Impact of Culture - Kashirov, Matvei (2025)
This research is dedicated to the influence of culture on entrepreneurial intentions of students. The Japanese cultural context is unique, and it is revealed in various values and artifacts. At the same time, entrepreneurial intentions of Japanese students are very low. This qualitative study aims to examine the influence of culture on entrepreneurial intentions through the extensive literature review and interviews.